President’s Message - Khotar, Rupinder (Operating Room Nurses Association of Canada Journal, 2014)
Service is a concept that is dear to me so I speak of it often. At the end of the year I, like many people, reflect on the year gone by. My work, my family and my friends are part of my inventory. I review my relationships and hope that I have served well in all aspects of my life. The kinship and fellowship experienced over the holidays strengthens these connections and amplifies their importance. Following the holidays I dream of opportunities as I stopped making resolutions many years ago.